Kemampuan Menulis Slogan Siswa Kelas VIIIA SMP Negeri 3 Kupang Tengah Tahun Pelajaran 2025/2026 - Yunifia Nelci Labati; Richard Oematan; Ona Diana Bani (Kampus Akademik Publiser, 2026)
The problem in this study is how the ability to write slogans of class VIIIA students of SMP Negeri 3 Kupang Tengah is. The objective to be achieved in this study is to describe the ability to write slogans of class VIIIA students of SMP Negeri 3 Kupang Tengah. The method used is descriptive qualitative. The research subjects were class VIIIA students, totaling 20 students of class VIIIA SMP Negeri 3 Kupang Tengah, consisting of 10 female students and 10 female students. The data collection technique was carried out through a slogan writing test with the theme of environmental cleanliness. The data were analyzed using the formula of mean and percentage. The results of the study on the ability to write slogans of class VIIIA students of SMP Negeri 3 Kupang Tengah classically based on the aspect of content suitability with the theme obtained a score of 88.75, the language aspect obtained 67.5, and the uniqueness aspect obtained 56.25, while the average score was 74. Individually, 5 students achieved the qualification of very capable, 5 students achieved the qualification of capable, 5 students achieved the qualification of fairly capable, and 5 students achieved the qualification of less capable. The ability to write slogans of class VIIIA students of SMP Negeri 3 Kupang Tengah obtained an average score of 74, categorized as capable. Based on these research findings, it can be concluded that class VIIIA students of SMP Negeri 3 Kupang Tengah already possess the ability to write slogans, particularly in conveying messages concisely, clearly, and easily understood.